Building Students' Character and Life Skills through the Islamic Religious Education Curriculum - Nada Nabilah; Juliani; Nida Khafia Lubis; Kristiana; Wahyu Rizqi Ardana (Journal of Contemporary Gender and Child Studies, 2024)
The emergence of increasingly sophisticated technology requires humans to optimize intellectually and morally. Education plays a role in producing a generation of intellectuals and noble characters. Islamic religious education is the basis for becoming a reference for the source of the actual value of power that can lead to the aspired activity, namely character education as the needs of the Indonesian nation. This study aims to examine character education through Islamic religious education in the era of the digital revolution. This study uses a qualitative method with the type of library research or library research. Researchers analyzed written literature as the primary source in books, research journals, and seminar proceedings. Based on this literature review, character education through Islamic religious education is based on religious values, Pancasila, culture, and national education goals. Implementing morality (character) in Islamic religious education through teaching, habituation, coercion, punishment, fosters student character.